Strategi Komunikasi Nuface Dalam Menarik Minat Generasi Z Pada Platform Tiktok Shop - Nurhidayah, Ismi; Anom, Erman (Jurnal Ilmiah Wahana Pendidikan, 2025)
A communication strategy is a plan made to achieve certain goals through the use of effective communication. Communication strategy plays a very important role in increasing sales and attracting the interest of Generation Z. Nuface's communication strategy in attracting the interest of Generation Z in Tangerang through the TikTok Shop platform can involve various approaches that are creative, relevant and adapt to the habits and preferences of this audience. This research aims to determine Nuface's communication strategy in attracting the interest of Generation Z in Tangerang on the TikTok Shop platform and to find out what are the inhibiting and supporting factors for Generation Z communication in their interest in buying Nuface products on the TikTok Shop platform. This research uses qualitative research with data collection techniques through interviews and documentation. The data analysis techniques used are data collection, data reduction, data presentation and drawing conclusions. The research results show that (1) Nuface's communication strategy in attracting the interest of generation Z through the TikTok Shop platform is relevant and interesting content, live shopping on the TikTok Shop application, creating attractive advertisements, and using the TikTok Shop feature. (2) The inhibiting factors for generation Z communication in their interest in purchasing Nuface products on the TikTok shop platform are the TikTok algorithm which changes frequently and lack of trust in the product. Meanwhile, the supporting factors for generation Z communication in their interest in purchasing Nuface products on the TikTok Shop platform are creative or visual content, and authenticity and originality.